(untitled) (LTU Journal of Advanced Computing & Engineering, 2026)
Smartphones have been fascinating digital gadgets, and everyone in the present digital generation desires to have one and get access to the services they offer. However, a sort of irrational anxiety or fear may arise when one is out of smart phone contact. The phobia that relates to no mobile phone is termed nomophobia. The study was designed with the objective of measuring the nomophobia level of teachers and students and determining whether or not there is any significant difference between the pattern of smartphone use and nomophobia. A correlational study was conducted among 195 participants (150 students and 45 teachers). Questionnaires related to demographic variables, patterns of smartphone use, and the nomophobia questionnaire (NMP-Q) are used for this purpose. The study showed that out of 45 teachers, 13 (28.9%) had severe nomophobia. Similarly, out of 150 students, 38 (25.3%) had severe nomophobia. However, the female gender showed a greater level of nomophobia than males. The use of smartphones for making calls, texting and chatting, connecting to social media, searching for information on the internet, listening to music and watching movies, gaming, and killing time had a significant effect on increasing nomophobia levels.